Techniques for transcatheter recanalization of completely occluded vessels and pathways in patients with congenital heart disease - Latson Larry; Qureshi Athar (Wolters Kluwer Medknow Publications, 2010)
Occlusions of major vessels in patients with congenital heart disease may occur due to a variety of factors. These occlusions are often felt to be best addressed surgically; however, we and others have been successful in recanalizing most of these vessels in the catheterization laboratory. Most of these patients will require multiple procedures in the catheterization laboratory to ensure vessel patency and to facilitate vessel growth. Physicians performing the procedure should have a thorough understanding of the anatomic considerations for the intended procedure and have access to a variety of devices and equipment to optimize the result of the procedure. In this article, we review some of the technical aspects that are vital for the success of the procedure.